CHANGES IN THE LOCAL COORDINATION OF TRACE RARE-EARTH ELEMENTS IN GARNETS BY HIGH-ENERGY XAFS: NEW DATA ON DYSPROSIUM - Quartieri S.; Dalconi M.C.; Boscherini F.; Oberti R.; D'Acapito F. (My University, 2004)
The site location and local geometry of trace amounts (299 ppm) of dysprosium in a natural melanite garnet from a carbonatitic rock have been studied by high-energy fluorescence-detected X-ray absorption fine-structure spectroscopy (XAFS). Measurements were done at the Dy K-edge (53789 eV). Data analysis shows that Dy (i.r. = 0.98 ) is incorporated at the X site, similarly to other REE, namely Nd (i.r. = 1.11 ) and Ce (i.r. = 1.14 ). Comparison of the XAFS data obtained for these three REE and for Ca shows that, within a given garnet composition, the difference in the local geometry can be modelled in terms of differences in the ionic radii. On the contrary, the local coordination of the individual cations is different in distinct garnet compositions, in contrast to what was suggested by previous atomistic simulations of the garnet structure. Comparison of the local coordination geometries available in the literature shows that the Young modulus of the X site strongly depends on the major-element composition of all the structural sites. Both these points are important for Earth Sciences, and especially for geochemical modelling of trace-element incorporation and partitioning.
Keywords: XAFS; Dysprosium; Garnet; Melanite